Multicloud service composition: A survey of current approaches and issues. Issue 10 (10th April 2018) - Lahmar, Fatma; Mezni, Haithem
Abstract: During the last decade, cloud computing became a natural choice to host and provide various computing resources as on‐demand services. To better satisfy user requirements, cloud services may be combined while considering the constraints of the virtualized environment, including security policies, resources availability, and interoperability. Extensive surveys have been conducted to study the major issues related to the cloud service composition problem. However, very few works have studied such issues in a multicloud setting. To fill this gap, we provide in this paper a systematic literature review on multicloud service composition. We start with a background on service composition in single clouds. Then, we present the multicloud taxonomy, and we study how service composition was tackled by researchers in multicloud environments. Finally, we identify the challenges and the requirements of multicloud service composition, as well as the future directions. Abstract : The proliferation of multicloud environments and the increasing complexity of cloud users' requirements have raised the need for effective cloud service reuse methods in the multicloud setting. Existing solutions lack facilities for multicloud service composition. In this paper, we perform a systematic literature review on multicloud service composition. We present the multicloud taxonomy. Then, we provide a categorization and a discussion of existing service composition approaches in multicloud environments. Finally, we identify the key requirements and the future directions.